Seismic anisotropy and mantle flow beneath Turkey - Polat, Gülten. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2006., 2006)
In this study, SKS and SKKS phases have been used for the analysis of shear wave splitting in order to investigate polarization anisotropy in the upper mantle beneath Turkey. To determine the shear wave splitting parameters (fast polarization direction and delay time), we have used teleseismic waveforms obtained from 21 broadband stations in Turkey. Shear wave splitting measurements are very important in determining the role of mantle flow in the geodynamics of the African-Arabian-Eurasian collison. The collision of the Arabian and African plates with Eurasia dominates the tectonic framework of the Eastern Mediterranean and Middle East (e.g., McKenzie, 1972; Jackson and McKenzie, 1988). The leading edge of the African plate is being subducted along the Hellenic trench at a higher rate than the relative northward motion of the African· plate, required that the trench moves southward relative to Eurasia proper (e.g., Sander and England, 1989; Royden, 1993). There are two adjacent subduction zones in the region: The Hellenic arc to the west and the Cyprian arc to the east. The Hellenic arc is characterized by a relatively steep, retreating subduction, whereas the Cyprus arc appears to involve a shallow subduction with two major seamounts (the Eratosthenes and Anixamander) impinging on the trench (Kempler and Ben-Avraham, 1987). Extension behind the Hellenic arc is arc-normal, whereas extension behind the Cyprus arc appears to be arc-parallel. Our results in Central Anatolia basically exhibits a NE-SW fast direction, while in Eastern Anatolia we have found a NE-SW fast direction and lag time consistent with the results obtained from temporary broadband stations of the eastern Turkey Seismic Experiment project within the Anatolian plate (Sandvol, 2003). These observations indicate that the anisotropic fabric could be relatively uniform throughout the upper mantle beneath the Anatolian plate. However, in the western Anatolia we have found a N-S fast direction that shows consistency with the directions of lithospheric extension inferred from GPS data. We have also found some evidence of trench parallel mantle flow as inferred from our results and those of Hatzfeld et al. (2001). Given the thin and hot lithospheric mantle beneath Turkey, it is unlikely that any of the observed anisotropy can be attributed to "frozen" or "fossilized" LPO induced splitting. Therefore, we believe that these observed changes in splitting reflect the variations in the asthenospheric flow along the AfricanAnatolian plate boundary.
Keywords: Earth (Planet) -- Mantle -- Turkey.; Plate tectonics.